Characterisation of a High Fibre Flour Prepared from Soy Milk By-Product and Its Potential Use in White Wheat Bread - Philip Davy; Timothy Kirkman; Christopher J. Scarlett; Quan Vuong (Foods, 2022)
The commercial production of soy milk renders a large quantity of wet soybean by-product (SMB), which is typically dumped, incinerated, or partially used as animal fodder. This wet SMB has a high moisture content that is rich in nutritional and biologically active compounds. This study aimed to characterise the composition and properties of a flour milled from SMB dried at 100 °C (SMB100) and assess its possible application as a fibre substitute in white bread. The results showed that SMB100 has high levels of dietary fibre (40.6%) and protein (26.5%). It also contains high levels of saponins (31.4 mg/g) and isoflavones (698.0 µg/g). SMB100 has a light-yellow colour with low moisture content and water activity (8.2% and 0.55, respectively). The results also indicated that replacement of wheat flour with SMB100 at 10 or 12.5% by flour weight negatively impacted the raising volume, density, and texture of white bread. Alternatively, substituting wheat flour with 5% of SMB100, did not significantly impact the physical properties of white bread, while significantly improving its dietary fibre content in comparison with the control, revealing that SMB100 is a potential substitute of wheat flour for improvement of dietary fibre in bread. Future studies are needed to optimise bread formulation and improve the processing condition which produces quality white bread with high dietary fibre using SMB100.